A Review of Recent Patents on LoRaWAN - Wu, Qing (Recent Patents on Engineering, 2024)
Background: LoRaWAN technology enables IoT devices with ubiquitous connectivity, which further empowers a broad spectrum of applications, including civil engineering, agriculture, and smart home. Although LoRaWAN has low-power energy consumption and long-range communication capability, it has many features that should be carefully managed to improve its performance. Objective: This paper aimed to review recent patents on improving the performance of LoRaWAN. Methods: The most related patents on improving the performance of LoRaWAN were discussed and analyzed. Results: A total of 71 patents were reviewed. This paper proposed a 2D taxonomy to categorize the existing patents. These patents aimed at focusing on the main components of LoRaWAN, i.e., end node, gateway, and server, and improving the performance of LoRaWAN from six aspects, i.e., energy efficiency, communication range, transmission efficiency, collision management, network security, and interoperability. The methodologies used in the current patent development were also discussed. Conclusion: Tremendous efforts have been devoted to improving the performance of LoRaWAN in recent years. To continue the growth of LoRaWAN technology, future patent development may focus on scalability, cost-effectiveness, and ease of implementation.
Keywords: interoperability